Entrepreneurial role models and college students’ entrepreneurial calling: A moderated mediation model - Dongmei Jin; Xiaomeng Liu; Fuqin Zhang; Zhiyi Wen (Frontiers in Psychology, 2023)
IntroductionCollege entrepreneurship education should not only cultivate a group of college students who have strong willingness to start a business immediately after graduation, but also pay attention to future entrepreneurship success of college students. Correspondingly, in addition to attaching importance to improving college students’ entrepreneurial intention, college entrepreneurship education should pay attention to improving college students’ entrepreneurial calling. At present, there is insufficient research on the association between entrepreneurial role models and entrepreneurial calling. We aim to study the mechanism and boundary condition of the association between entrepreneurial role models and entrepreneurial calling.MethodsA longitudinal survey was distributed among 519 students from 16 colleges and universities in China. In the survey, the college students answered questions on entrepreneurial role models, entrepreneurial calling, entrepreneurial perceived behavioral control and entrepreneurial hands-on practice. Hierarchical regression was conducted, testing the association between entrepreneurial role models and entrepreneurial calling of college students, mediated by entrepreneurial perceived behavioral control and moderated by entrepreneurial hands-on practice.ResultsTherefore, based on the social learning theory, the theory of planned behavior and the entrepreneurial event model, and by hierarchical regression of the data, this study confirmed that entrepreneurial role models were positively associated with college students’ entrepreneurial calling by partially mediating with entrepreneurial perceived behavioral control. Moreover, Entrepreneurial hands-on practice positively moderated not only the relationship between entrepreneurial perceived behavioral control and entrepreneurial calling, but also the mediating association of entrepreneurial perceived behavioral control between entrepreneurial role models and entrepreneurial calling.DiscussionThis study not only enriches the theoretical research on entrepreneurial calling and entrepreneurial role models, but also provides valuable educational enlightenment for colleges and universities to improve the students’ entrepreneurial calling.